A Prospective Investigation of Bispecific CD19/22 CAR T Cell Therapy in Patients With Relapsed or Refractory B Cell Non-Hodgkin Lymphoma - Zhang, Ying; Li, Jiaqi; Lou, Xiaoyan; Chen, Xiaochen; Yu, Zhou; Kang, Liqing; Chen, Jia; Zhou, Jin; Zong, Xiangping; Yang, Zhen; Li, Minghao; Xu, Nan; et al. (Frontiers in Oncology, 2021)
Background: The use of T cells expressing chimeric antigen receptor T (CAR T) engineered to target CD19 constitutes breakthrough treatment for relapsed or refractory B cell non-Hodgkin lymphoma (R/R B-NHL). Despite improved outcomes, high relapse rate remains a challenge to overcome. Here, we report the clinical results and the pharmacokinetics of bispecific CD19/22 CAR T in patients with R/R B-NHL. Methods: We performed a prospective, single-arm study of bispecific CD19/22 CAR T cells in R/R B-NHL. We analyzed the safety and efficacy and investigated the kinetic profiles of the CAR T cells. CAR transgene levels were measured using quantitative polymerase chain reaction, and correlation analyzes of pharmacodynamic markers and product characteristics, disease conditions, clinical efficacy and adverse events were performed. Results: From August 2017 to September 2020, a total of 32 patients with CD19/22 CAR T administration were analyzed. The overall response rate was 79.3%, and the complete response rate was 34.5%. The progression-free survival (PFS) and overall survival (OS) rates at 12 months were 40.0% and 51.8%, respectively. Among patients who had a CR at 3 months, the PFS and OS rates at 12 months were 66.7% and 75.0%, respectively. Severe cytokine release syndrome (sCRS) (grade 3 and higher) occurred in 9 patients (28.1%). Grade 3 or higher neurologic events occurred in 4 patients (12.5%). One patient died from irreversible severe CRS-associated acute kidney injury. Long-term CAR T cells persistence correlated with clinical efficacy (133 days vs 22 days, P=0.004). Patients treated with more than 3 prior therapies and presenting extranodal organ involvement had lower maximal concentration (Cmax) values than other patients. Responders had higher Cmax and area under the curve values than non-responders. Tumour burden and Cmax were potentially associated with the severity of CRS. Conclusions: This study demonstrates the safety and potential clinical efficacy of bispecific CD19/22 CAR T cells in patients with R/R B-NHL and highlights the importance of measuring kinetic parameters in PB to predict efficacy and safety in clinical applications of CAR T cell therapy. Trial registration: NCT03196830. Registered June 23, 2017. https://www.clinicaltrials.gov/ct2/show/NCT03196830.